Home bank intermediation of foreign direct investment - Steven Poelhekke (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper investigates the benefits of banks' direct investment in foreign subsidiaries and branches for non-financial multinationals. The paper builds on the literature on international banks which has primarily focused on the implications for host countries, rather than for its international clients, and on the literature on foreign direct investment (FDI), which emphasizes significant costs of investment. Using a new detailed data set of non-stationary sector-level outward FDI, this paper finds that the volume of FDI by home market banks boosts FDI by non-financial firms from the same home market. Domestic and third-country foreign banking provide imperfect substitutes, especially in countries that are corrupt or have weak rule of law. The result rests on banks' FDI in local branches and subsidiaries rather than cross-border lending. These findings are consistent with a role for home market multinational banks in intermediating information asymmetry in opaque foreign markets. The sale of a major international bank to third-country counter parties during the recent crisis may thus result in persistently lower volumes of outward FDI from the bank's home market.
Keywords: F21; G21; O16; C33; 330; outward sector-level FDI; banks; asymmetric information; panel non-stationarity